Mechanistic Studies on Water‐Exchange Reactions in [Zn(H2O)4L]2+·2H2O for L = sp2, sp3 Oxygen‐Donor Ligands: A DFT Approach1. Issue 12 (20th February 2013) - Alzoubi, Basam M.; Walther, Markus; Puchta, Ralph; van Eldik, Rudi
Abstract: Water‐exchange reactions on the five‐coordinate complex [Zn(H2 O)4 (L)] 2+ · 2H2 O (L = water, methanol, ethanol, propan‐1‐ol, butan‐1‐ol, dimethyl ether, propan‐2‐ol, fluorophosgene, phosgene, formaldehyde, acetyl chloride, acetaldehyde, acetone and acetamide) were studied by quantum‐chemical calculations (B3LYP/6‐311+G**). The reactions follow an associative pathway that involves the formation of a six‐coordinate intermediate [Zn(H2 O)5 (L)] 2+ · H2 O, followed by the dissociation of a water molecule to form the product [Zn(H2 O)4 (L)] 2+ · 2H2 O. The water‐exchange process involves isoenergetic cis ‐ and trans ‐oriented transition states to form the product state that is similar to the reactant state. Of the studied ligands L, acetamide, which has the highest basicity, exhibited the highest activation energy and energy gap between the reactant and intermediate states. Electronic and steric effects of the coordinated ligands influence the activation barrier and the efficiency of the water‐exchange process. Abstract : The water‐exchange mechanism of [Zn(H2 O)4 L] 2+ · 2H2 O (L = O‐donor ligands) has been studied by DFT calculations (B3LYP/6‐311+G**). The calculated energy values and structural data provide theoretical evidence that the water‐exchange process follows an associative reaction mechanism that involves two reaction steps and the formation of a six‐coordinate intermediate [Zn(H2 O)5 L] 2+ · H2 O.